Method for achieving accounting subject dynamic calculation in star-shaped model - ZHOU XINXIN (2016)
The invention discloses a method for achieving accounting subject dynamic calculation in a star-shaped model. According to the implementation process, the method comprises the steps that firstly, a calculation formula is imported, in other words, the calculation formula is imported in a database in a manual or filling mode; then, calculation factors are extracted, and a calculation sequence of target subjects is generated according to the calculation factors; according to the content, an SQL for calculation of the target subjects is generated and stored. Compared with the prior art, according to the method for achieving accounting subject dynamic calculation in the star-shaped model, it is not needed that development personnel compile the SQL according to a formula provided by accounting service personnel, and then generate SQL processing logic conforming to the star-shaped model by configuring a program; The method is especially suitable for the scene where a large quantity of accounting subjects need to be